Features of structural and functional changes of the brain in patients with schizophrenia - S. A. Galkin; E. G. Kornetova; A. N. Kornetov; D. A. Petkun; N. A. Bokhan (Бюллетень сибирской медицины, 2025)
Aim. To establish the features of structural and functional changes in the brain in patients with schizophrenia.Materials and methods. A morphometric analysis of the brain using MRI scans was performed, along with a clinical assessment of the electroencephalogram (EEG) of 35 patients with schizophrenia (20 men and 15 women). The control group included 18 healthy sex- and age-matched individuals (10 men and 8 women). Statistical processing was carried out using the χ2 test, the Fisher’s exact test, and the Spearman’s rank correlation coefficient.Results. Compared to the control group, patients with schizophrenia were significantly more likely to show signs of ventricular dilation (p = 0.039), asymmetry of the lateral ventricles (p = 0.041), periventricular edema (p < 0.001), and enlargement of the subarachnoid space of the cerebellum (p = 0.004). Changes (class >1A) in the functional activity of the brain in the group of patients with schizophrenia were detected in 65.7% of the cases. In more than half of the cases, patients with schizophrenia showed decreased bioelectric activity of the brain (class 2 in 48.6% and class 3 in 11.4%); at the same time, EEG signs of paroxysmal activity were detected in a few patients (class B in 11.4% and class C in 5.7%) (p < 0.001). A statistically significant direct correlation was found between the enlargement of the subarachnoid space of the cerebellum and paroxysmal EEG activity in patients with schizophrenia (r = 0.377; p = 0.044).Conclusion. The findings of our study highlight that the combined use of MRI and EEG can provide important information about brain pathology in schizophrenia. The data obtained are also important for testing the hypothesis on the association between vascular and functional disorders of the brain in patients with schizophrenia.